Performance limitations of a Banyan-based ATM switching system under multiple, shaped traffic flows - Carvalho, Paulo (1998)
The asynchronous transfer mode (ATM) is gradually taking a prominent role in the provision of broadband communication services worldwide. Based on a cell technology, ATM is expected to integrate efficiently both real-time and non-real-time traffic, while providing quality of service guarantees per connection. In this scenario, the performance evaluation of network elements assumes a vital role. This paper concentrates on the behaviour of an ATM switching system when carrying block-based traffic, studying the effects which the periodicity inherent to certain traffic patterns may have for the performance of ATM networks and systems. Traffic presenting a regular, block-based structure may result from traffic shaping actions taken by an ATM source. In particular, the interaction of periodic, bursty traffic flows, like MPEG video, is studied by using simulation and experiments. The network model consists of multiple ATM user terminals connected by a blocking, input-buffered ATM switch[Leslie91] operanting synchronously on a cell basis. Each terminal is able to multiplex several traffic sources providing, if required, shaping facilities. MPEG video traffic is generated using a slice-based model with two periodicity levels. The length of the slices follows a Gamma distribution. The results show that for concurrent traffic flows the switch, which implements an independent round-robin scheduling algorithm on a switching element basis, can be extremely unfair for some traffic patterns. In fact, a traffic flow can be significantly delayed comparing to other competing flows. In the presence of MPEG video, the scheduling process can be influenced by a memory effect which can persist over several frames. The results also show that when shitching multiple concurrent MPEG flows, the variation of frame starts in the different flows has to be taken into account, or resource requirements may be underestimated.